PROSPECTS FOR DEVELOPING THE ECONOMIC EFFICIENCY OF COMMERCIAL BANKS THROUGH DIGITAL SERVICES (Marketing Journal, 2025)
The article analyzes the current state of use of digital technologies in the activities of commercial banks in Uzbekistan and identifies problems that hinder economic efficiency. At the same time, practical proposals and recommendations were put forward to eliminate these problems and increase the efficiency and economic effectiveness of banking services through the introduction of digital technologies.
Keywords: commercial banking; economic efficiency; digital technologies; profitability index; foreign experience